1994
DOI: 10.3382/ps.0731673
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Triphosphate Bioluminescence as a Method to Determine Microbial Levels in Scald and Chill Tanks at a Poultry Abattoir

Abstract: According to Hazard Analysis of Critical Control Points (HACCP) programs developed for the poultry industry, poultry processing waters should be actively monitored to minimize cross-contamination between chicken carcasses. In order to monitor HACCP programs, a test is required that provides results on a real time basis. A modified adenosine triphosphate (ATP) bioluminescence test has been developed that can assess microbial levels in poultry processing waters within 15 min. A study was conducted to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…1997). Test results showed that the sensitivity of the MDTCS to detect microorganisms in water was higher than the one reported by Bautista et al (1994). Previous studies using ATP Bioluminescence assays, reported minimum detectable levels of 100 CFU.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…1997). Test results showed that the sensitivity of the MDTCS to detect microorganisms in water was higher than the one reported by Bautista et al (1994). Previous studies using ATP Bioluminescence assays, reported minimum detectable levels of 100 CFU.…”
Section: Resultsmentioning
confidence: 64%
“…However, the MDTCS was able to determine the number of Pseudomonas aeruginosa colonies present in each of the spiked water samples within 24 h. The MDTCS was found to be accurate and reproducible for determining the Total Aerobic Count of water samples from three different water systems by using a 24 h incubation period. Several reports have shown that ATP Bioluminescence assays compared favorably to plate counting procedures for estimating the microbial load in milk, meat, and water tanks (Bautista et al 1992;Bautista et al 1994;Bautista el al. 1997).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of firefly luciferase to detect ATP is an established technique for monitoring microorganism growth (Bautista et al 1994;Brovko et al 1999). Previously, we constructed a genetically modified Photinus pyralis luciferase that generates 10-fold or higher luminescent intensity than the wild-type enzyme (Noda et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The use of firefly luciferase to detect ATP is an established technique for monitoring microorganism growth (Bautista et al 1994;Brovko et al 1999). However, this technique has a detection limit of approximately 100-10,000 cells in an analyte, which does not provide sufficient sensitivity for some industrial and clinical applications.…”
Section: Introductionmentioning
confidence: 99%